New Media Abuse and Hoax in Ma'nai Harfi and Ma'nai Ismi Perspective: A Study of Badi'uzzaman Sa'id Nursi Thought - Adeni Adeni; Abdul Karim; Osman Koroglu (TSAQAFAH, 2021)
This article aims to examine the use of the ma'na-yi harfi ‎(Indicative Meaning) and ma'na-yi ismi ‎(Nominal Meaning)‎ concept of ‎Badiuzzaman Said Nursi in preventing hoaxes caused by new media abuse. The approach offered ‎by Nursi is important because it can be considered as the basis of Islamic media communication ‎in which moral values in media are prioritized over only material aspects. New media ‎characterized by openness and freedom, in a certain condition, enable the hoax to spread. Hoax ‎often occurs because the media does not prioritize morality values but leads to materially self and ‎group fulfillment. Using the qualitative method with library data in the form of Said Nursi's ‎Risale-i Nûr, we explore Nursi's views related to ma'na-yi ismi and ma'na-yi harfi in the media ‎field. We then use his view as a basis for analyzing media hoaxes. The result is that the ma’na-yi ‎ismi perspective tends to be a worldly material orientation in which communication phenomena, ‎such as events, news, and information themselves, are understood based on the visible social ‎contexts where media practitioners are working and oriented to fulfill self-desires. Meanwhile, in ‎the ma'na-yi harfi perspective, the communication phenomenon is interpreted, constructed, and ‎displayed with self-consideration (individual or collective self), but it is built in the full ‎awareness that phenomena belong to the absolute Ruler (God), and humans as the giver of ‎meaning to those phenomena must translate the greatness of God in them. The phenomenon of ‎communication is considered a part of the greatness of God in the universe so the hoaxes and ‎negative messages can be avoided. The ma’na-yi harfi perspective can be considered as a solution ‎to solve the social problems of hoaxes.